2016
DOI: 10.1039/c5sm02820e
|View full text |Cite
|
Sign up to set email alerts
|

Response of biopolymer networks governed by the physical properties of cross-linking molecules

Abstract: In this study, we examine how the physical properties of cross-linking molecules affect the bulk response of bio-filament networks, an outstanding question in the study of biological gels and the cytoskeleton. We show that the stress–strain relationship of such networks typically undergoes linear increase – strain hardening – stress serration – total fracture transitions due to the interplay between the bending and stretching of individual filaments and the deformation and breakage of cross-linkers. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Also, the failure of individual polymers which involves breaking down complicated macromolecular structures [52], is much more complicated than the simple threshold we used. Both these effects make it more likely for the network to focus stress and crossover to crack nucleation in the thermodynamic limit [34,35]. The critical regime we found for p < p c may be observable in man-made materials in which bending stiffness and threshold are controlled to be very small.…”
mentioning
confidence: 89%
“…Also, the failure of individual polymers which involves breaking down complicated macromolecular structures [52], is much more complicated than the simple threshold we used. Both these effects make it more likely for the network to focus stress and crossover to crack nucleation in the thermodynamic limit [34,35]. The critical regime we found for p < p c may be observable in man-made materials in which bending stiffness and threshold are controlled to be very small.…”
mentioning
confidence: 89%
“…Considering natural biopolymer networks, the majority of studies have focused on reconstituted actin networks, crosslinked with different natural crosslinking proteins (Claessens et al, 2006;Schmoller et al, 2008;Schmoller et al, 2009;Lieleg et al, 2011) or synthetic crosslinking modules (Lorenz et al, 2018). These studies have shown that the crosslink properties (kinetics and stiffness) affect network topology, elastic modulus as well as stress relaxation and aging (Claessens et al, 2006;Schmoller et al, 2008;Schmoller et al, 2009;Lieleg et al, 2011;Strehle et al, 2011;Wei et al, 2016). Analogous studies aimed at understanding the effect of crosslink kinetics on viscoelastic material responses have been performed for a number of synthetic polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cross-linking proteins are very flexible 58 60 , their stabilizing effect by increasing the interpenetrating connectivity in the branched actin network is rather distinct. The branched actin network with a low density of cross-linking proteins is incapable of supporting the propulsion force for cell motility.…”
Section: Resultsmentioning
confidence: 99%
“…The diameters and elastic properties of actin filaments and cross-linking proteins are obtained from refs. 58 , 60 , 88 , 89 , as shown in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%